Design of an Accounting Information System in Preparing Financial Reports for Micro, Small and Medium Enterprises - Mervita, Eda; Eviatun, Esti; Hasan, Saukani (Institut Bisnis dan Informatika Kesatuan, 2024)
The problem in this research is how the sales information system works in preparing financial reports in accordance with SAK ETAP in one of the micro, small and medium enterprises in the 16 markets of Palembang city, namely Bella Store. The aim is to create an accounting information system for preparing appropriate financial reports in accordance with SAK ETAP at the Bella Store at Pasar 16 Palembang. The data analysis in this research is a qualitative analysis by collecting and compiling financial reports starting from evidence of daily recording and evidence of goods purchase data to produce financial reports. The results of the analysis show that Bella Store does not yet have an accounting system. Bella Store makes financial reports which are used as company managers and financial accountability to parties outside the company . Keywords: Accounting, Finance, Reports, Sales, Systems